Pendampingan Strategi Pemasaran pada UMKM Keripik Cijanggot dalam Meningkakan Penjualan - Rifki Abdul Malik; Irma Megawati; Arief Mulyawan Thoriq; Dede Supendi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Chips are a food that is loved by Indonesian people. Chips are a favorite snack and there are many different types and variants. In Purwakarta there is a famous MSME Chips called Cijanggot Chips. To be precise, it comes from Cipinang Village, Cibau District. There are several products from Cijangot Chips, namely cassava chips, potato chips and chocolate banana chips. In its business activities, Cijanggot Chips UMKM still uses traditional methods, namely by marketing manually to distribution locations such as food stalls and souvenir shops since 2015. The marketing strategy implemented by the Cijanggot Chips owner can be said to be quite good. However, in this modern era, it is very important to carry out marketing strategies through online media in order to increase sales and have a wider reach to consumers. There are several marketing strategies that can be used to increase product sales, namely by product innovation, online marketing, through social media and opening branches in new places.